In-situ synthesis and reaction mechanism of MgAlON in Al2O3-MgO composites produced in flowing nitrogen. Issue 17 (1st December 2017) - Yan, Mingwei; Li, Yong; Li, Ling; Sun, Yang; Tong, Shanghao; Sun, Jialin
Abstract: Al2 O3 -MgO composites were calcined in flowing nitrogen at 1700 and 1800 °C. The calcined Al2 O3 grains and powders were in-situ transformed into MgAlON and Al2 O3 grains showed numerous transgranular pores due to the decomposition of impurities such as SiO2, Fe2 O3, and Na2 O. The reaction mechanism of MgAlON was described as follows. Al2 O3 reacted with MgO with increasing temperature above 1000 °C to form MgAl2 O4 and was further transformed into Al2 O3 -rich spinel according to the reaction Al 2 O 3 ⟶ MgO ⋅ Al 2 O 3 2Al Mg + V Mg ′ ′ + 3 O O . MgO became unstable and decomposed into Mg (g) and O2 (g) owing to the oxygen consumed according to the C-O2 reaction, and Mg (g) diffused and transferred along pores or gaps in the material, reacting with Al2 O3 grains and powders or Al2 O3 -rich spinel to form spinel and Al (g). Al (g) was then nitrided into AlN, which dissolved into the spinel thus forming MgAlON.